Prosedur Penyimpanan Sayur Dan Buah dalam Menunjang Sistem Fifo Di Kitchen pada Hotel Taum Resort Bali Petitenget Kuta - Ni Luh Diana Wati; I Ketut Eli Sumerta Sumerta; I Made Sunata (HARMONY HOSPITALITY, 2025)
The research deals with the storage of Vegetable and Fruit Procedures to Support the FIFO System in the Kitchen at the Taum Resort Bali Hotel, Petitenget, Kuta, Bali. Threre are 3 problem formulations namely: (a) The procedure for storing vegetables and fruit to support the FIFO system in the kitchen at the Taum Resort Bali Hotel, Petitenget, Kuta, Bali, (b) the obstacles encountered in the Vegetable and Fruit Storage Procedures and (c) the solution to the obstacles.  The data collection technique used by are observation, interviews with Commis regarding the Vegetable and Fruit Storage Procedures in Supporting the FIFO (First in First Out) system, and Documentation carried out by taking pictures of how the storage of vegetables and fruit is carried out at the Taum Resort Bali Hotel The data analysis technique used is descriptive qualitative to lead to get the results and conclusions.  The research found out three conclusions; (a) the Vegetable and Fruit Storage Procedures in the Kitchen at the Taum Resort Bali Hotel have been implemented well, but there are still some errors that occur, such as lack of knowledge of kitchen staff regarding the application of the FIFO system which causes vegetables to rot, lack of knowledge in using tools that result in room temperature changing often so that vegetables and fruit rot faster, and lack of knowledge in the ordering process.